Pengaruh Pendidikan dan Pelatihan (Diklat) dan Pengalaman Kerja Terhadap Prestasi Kerja dan Pengembangan Karir Pada Karyawan Baleka Beach Resort Badung - Nugraha, I Gusti Ngurah Widia; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen, 2014)
Normal 0 false false false EN-US X-NONE X-NONE This research was conducted to know how education and training also work experience influences the work achievement and employee career development in Baleka Beach Resort. Source of data used are primer data and this research respondents are 56 employees who already have career experience. Data analysis used is path analysis. Based on data analysis can be stated that education and training, and work experience have influences to work achievement and the employee career development at Baleka Beach Resort.
Keywords: work experience, work achievement and career development